L. Testa, glassblower, at work at U.S. Department of Agriculture (1931)
General view of a glassblower, identified as L. Testa, working in an unidentified U.S. Department of Agriculture facility. Per a 1931 list of technical workers in the Department of Agriculture, Testa worked as a glassblower in the Biological and Organic Division, Fertilizer and Fixed Nitrogen Investigations, Bureau of Chemistry and Soils.
Keywords: Nitrogen fertilizer industry; Nitrogen--Fixation; United States. Bureau of Chemistry and Soils; United States. Department of Agriculture; Employees; Glass blowing and working; Testa, L.